2020
DOI: 10.12680/balneo.2020.388
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation in Osteoporosis - therapeutic chalenge?

Abstract: Introduction. Osteoporosis is a disease of the entire skeleton, characterized by decrease bone mass and microarhitectural alterations of bone tissue, which result in increased bone fragility and predisposition to bone fractures. Materials and methods. Accesing standard medical databases: Medline, Embase, Database, Pubmed and the Cochrane Register of Controled Studies to review new pharmacological studies and non-pharmacological terapies in osteoporosis. Statistical analysis performed from the data extracted fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Glazachev's study from 2017 demonstrated that blood glucose was significantly lower at one-month follow-up after intermittent hypoxia-hyperoxia therapy (12). Clinical research indicates that there is a common occurrence of disturbed glucose metabolism, often manifesting as increased blood glucose levels, even when grade 1 obesity is not specifically mentioned (15).…”
Section: Discussionmentioning
confidence: 99%
“…Glazachev's study from 2017 demonstrated that blood glucose was significantly lower at one-month follow-up after intermittent hypoxia-hyperoxia therapy (12). Clinical research indicates that there is a common occurrence of disturbed glucose metabolism, often manifesting as increased blood glucose levels, even when grade 1 obesity is not specifically mentioned (15).…”
Section: Discussionmentioning
confidence: 99%